The Wicked Marquis - Oppenheim, Edward Phillips (Saga Egmont, 2021)
As tenants and estate owners, the lives of the Marquis of Mandeleys and the Vont family have been intertwined for generations. The relationship has turned sour in recent years, following the Marquis' interest in current tenant Richard Vont’s daughter Marcia. Taking her to America, the Marquis set her on a path to a successful career as a writer, but Vont remains suspicious of his intentions and is hurt at being abandoned by his daughter. Bitter and lonely, he has devoted his life to destroying the Marquis and now plots his downfall. An intriguing story of jealousy, love, and revenge from author E. Phillips Oppenheim.